The UNC5C T835M mutation associated with Alzheimer’s disease leads to neurodegeneration involving oxidative stress and hippocampal atrophy in aged mice - Devi Krishna Priya Karunakaran; Makenna Ley; Joanna Guo; Ammaarah Khatri; Katherine Sadleir; Jelena Popovic; Arun Kumar Upadhyay; Jeffrey Savas; Daniele Procissi; Jasvinder Atwal; Robert Vassar (Molecular Neurodegeneration)
Abstract Alzheimer’s disease (AD) is characterized by amyloid plaques, neurofibrillary tangles, and synaptic and neuronal loss. Recently, a rare autosomal dominant coding mutation, T835M, in the Un-coordinated 5c (UNC5C) netrin receptor gene was segregated with late-onset AD (LOAD). Overexpression of T835M in primary hippocampal neurons increased cell death in response to neurotoxic stimuli including beta-amyloid (Aβ) suggesting a mechanism by which T835M may confer increased risk of LOAD. However, the molecular mechanism of T835M-mediated cell death remained under explored. Toward this end, we generated a mouse T835M knock-in (Unc5c KI/KI ) model and employed biochemical and histological analyses to understand the molecular mechanism of T835M-mediated pathogenesis in late onset Alzheimer's disease. We show that homozygous KI mice have significantly reduced hippocampal volume, increased ventricular volume, dendritic disorganization (CA1 region) and reduced UNC5C protein level by 12–18 months of age. Further, we show that the neuronal cell death is observed in the Unc5c KI/KI mice by 12 months of age by TUNEL analysis and activated Caspase 3/7 assay. Proteomic analysis of hippocampal samples showed upregulation of oxidative stress and downregulation of chaperone proteins at 18 months corroborating the biochemical and histological results showing increased c-Jun N-terminal Kinase (JNK) phosphorylation, NADPH oxidase, and decreased Netrin1 levels. Moreover, Unc5c KI/KI mice also show morphological changes in the astrocytes with increased number of branched processes, reduced GFAP levels, and significantly increased activation of microglia. Overall, these results suggest that T835M mutation causes neurodegeneration by creating an oxidative stress environment leading to synaptic degeneration and weakened astrocytes, thereby leading to neuronal cell death via apoptosis. Furthermore, to assess the effects of amyloid pathology on the mutation, we crossed Unc5c KI/KI mice with App NL−G−F/NL−G−F mice and observed an exacerbation of mutation-associated changes along with increased levels of Aβ42, suggesting that the T835M mutation increases the susceptibility of neurons to cell death and elevated Aβ42 levels, thus promoting AD pathogenesis. Understanding the molecular mechanism of cell death in regions susceptible to neurodegeneration such as the hippocampus could shed light on the players and pathways involved in cell death in AD pathogenesis and therefore could inform therapeutic approaches for AD.